Risk factors in the prediction of long‐term patency of Resonance metallic ureteric stent in malignant ureteric obstruction. Issue 2 (22nd April 2020) - Ho, Brian S. H.; Chiu, Peter K. F.; Lam, Wayne; Wong, Julius H. F.; Wong, Charles K. W.; Lai, Terence C. T.; Tsang, Chiu‐Fung; Ng, Ada T. L.; Chan, Chi‐Kwok; Ma, Wai‐Kit; Ng, Chi‐Fai; Tsu, James H. L.
Abstract: Objectives: Cancer is the second leading cause of death globally in 2018 with an estimated 9.6 million deaths. The costs of managing malignant ureteric obstruction (MUO) is a significant burden to any healthcare system. However, the management of MUO has long been a challenge for urologists. The standard options of percutaneous nephrostomy or polymer double J stents are fraught with problems. We report a large patient series with long‐term follow‐up in the use of Resonance metallic ureteric stents to relieve MUO, and identification of risk factors associated with stent failure. Patients and methods: All patients with MUO who were arranged to have Resonance metallic ureteric stent insertion at two university hospitals were included in this cohort study, starting from June 2011 to July 2016. Data were retrieved retrospectively. The primary outcome was the total duration of stent patency before stent failure due to malignant disease progression. Stent failure was defined as ureteric obstruction identified on imaging (functional radioisotope scan or antegrade pyelogram), acute renal failure resolved by subsequent percutaneous nephrostomy, or any other cause requiring stent removal prematurely. Secondary outcomes were identification of factors associated with stent failure, grade III or above complication, and development of a risk‐adopted model to predict metallic ureteric stent patency rates in MUO patients. Median duration of functioning metallic ureteric stent was determined with Kaplan‐Meier survival curve. Results: A total of 124 renal units in 95 patients with MUO were eligible for the study, with a median follow‐up period of 22.9 months. About 106 (85.5%) renal units had successful metallic stent insertion, of whom 41 (33.1%) renal units ultimately progressed to ureteric obstruction despite the metallic stents, and required subsequent insertion of nephrostomies. Median duration of functioning metallic ureteric stents was 25 months. Female gender (HR 3.0, 95% CI: 1.3‐7.2, P  = .014) and suspicious bladder lesion (HR 2.9, 95% CI: 1.4‐6.2, P  = .005) were independent risk factors for stent failure, respectively. Stratifying patients into low (0 risk factor), intermediate (1 risk factor), and high (2 risk factors) risk groups, we found that this could predict the duration of stent patency in MUO with the metallic stents. (Low risk: 30.3 months vs intermediate group: 17.8 months vs high risk: 4.9 months, P  < .001). Conclusion: Resonance metallic ureteral stents are able provide a median of 25 months of ureteric drainage in patients with MUO. Determining whether a patient has one or both risks factors (female gender and bladder lesion) will allow one to estimate the duration of metallic stent patency, which in turn may aid in determining cost‐effectiveness in individual patients.